Nova lei de licitações e contratos : perfil profissiográfico e mapeamento das competências para as funções essenciais de compras governamentais nos municípios sergipanos - Almeida, Daniel da Silva (2022)
The present study aimed to clarify Sergipe municipal managers about the need to adopt management by competence with public servants directly and indirectly involved in the government procurement process, in order to meet the requirements proposed by the New Law on Bidding and Contracts - Federal Law No. 14,133/2021. In this sense, constitutional and legal provisions relevant to the matter were presented, aiming at its delimitation, aggregated by doctrinal understandings. As municipal management must observe the implementation of management by competence, it is imperative to know its human capital, where we proposed an analysis of the professional profile and consequent mapping of competences of those public agents capable of performing the essential functions of government procurement, also highlighting the requirement about of these will be occupied only by effective civil servants or by public employees belonging to the permanent staff of the Public Administration. Analyzing the world scenario and, later, the national scenario, focusing on public governance to the importance of competency management, we demonstrate the need to understand public procurement in order to focus solely on the professional profile of public agents and the mapping of municipal servants to performance of their attributions, raising the need for continued training. At a time, evaluating the normative about the framework of regulation as general or specific, the study was started, limited geographically in the light of State Decree No. 24,338 of April 20, 2007, comparing municipalities of the 8 (eight) territories in Sergipe. The methodology has an exploratory objective, involving field research supported by the theoretical framework used. The way of approaching the problem used a qualitative methodology, considering the relationship between the objective and the subjective, through the interpretation of data collected in the field work. This study demonstrated not only the need for municipal managers to prepare for the changes brought about by Federal Law No. 14,133/2021, but also their technical staff, since most of them showed difficulty in knowing their own attributions, still under the regency of the laws to be repealed after the transition. Thus, in view of the results obtained with the surveys and interviews, dependent on future new regulations, it became possible to present as a final product a Technical Manual, aimed at management by competence within the scope of the Sergipe municipalities involved, given the peculiarity of the currently existing public agents. in them, which can spill over to other municipalities, given the uniformity of data obtained in different regions, providing subsidies for the optimization of future routines of government purchases.